Effect of physical exercise in patients whith COPD: A literature review (Research, Society and Development, 2023)
This research aimed to analyze the effects that exercise has on people with COPD. As a methodology, a literature review was adopted. We analyzed 10 articles published between 2013 and 2023, all collected from the SciELO, Pubmed and LILACS database resulting from the descriptors: Exercise, Pulmonary Recovery, Physical. Articles focused on investigating the influence and benefits that physical exercise has on patients living with Chronic Obstructive Pulmonary Disease (COPD) were analyzed with exercise approaches in different ways, such as weight training, walking and calisthenics. Among the main results found, it was possible to observe that physical exercise played an important role in the quality of life of many patients living with COPD, primarily in the pulmonary rehabilitation (BR) phase. Therefore, we arrive at the result that the effect of physical exercise on patients with COPD can be beneficial to prolong and maximize the quality of life of individuals who have this condition or are undergoing rehabilitation.